Intrinsic factor autoantibodies by luminescent immuno-precipitation system in patients with corpus atrophic gastritis - Ilaria Marzinotto (Elsevier, 2021)
Background: Corpus atrophic gastritis (CAG) may lead to intrinsic factor (IF) deficiency and vitamin B12 malabsorption. Intrinsic factor autoantibodies (IFA) are considered markers of pernicious anemia, but their clinical utility in CAG has not been evaluated. This study aimed to assess IFA in CAG patients and controls using a luciferase immunoprecipitation system (LIPS). Methods: Recombinant nanoluciferase-tagged IF secreted from transfected Expi293F cells was used as antigen in an IFA-LIPS assay. IFA IgG were measured in sera from subjects undergoing gastroscopy and biopsy (updated Sydney system) mainly for anemia (57%) or dyspepsia (34%). This cohort comprised 105 patients with histologically-proven-CAG (cases: median age 64 years, 68% females) and 110 subjects with suspected CAG that were histologically negative (controls: median age 67 years, 54% females). Cut-off values were selected by Q-Q-plot analysis (negative: <2.5 arbitrary units). Results: IFA levels were higher in cases than in controls (Mann-Whitney:p < 10−5). The ROC-AUC was 0.67 (95%CI 0.60–0.73, p < 0.0001). The IFA LIPS sensitivity and specificity for CAG were 32% (95% CI 24–42) and 95% (95% CI 90–99). This diagnostic performance remained similar after stratification for the presence/absence of anemia, dyspepsia or vitamin B12 deficiency. IFA levels were higher in females compared with males (p = 0.0127). In females aged <65 years, IFA-positives were more prevalent than in males (43.5% vs 6.6%, p = 0.011). Conclusions: The IFA-LIPS assay discriminated between CAG patients and controls showing a good specificity (95%) at the cost of sensitivity (32%). IFA-positivity occurred independently from anemia and vitamin B12 deficiency, but was more frequent in younger females. IFA testing should be considered in patients at high clinical suspicion of CAG.